Crosstalk between colorectal cancer cells and cancer-associated fibroblasts in the tumor microenvironment mediated by exosomal noncoding RNAs - Sun, Shichen; Zhang, Yanyu; Li, Yubing; Wei, Linlin (Frontiers in Immunology, 2023)
Colorectal cancer (CRC) is a common malignant tumor of the digestive system, and its morbidity rates are increasing worldwide. Cancer-associated fibroblasts (CAFs), as part of the tumor microenvironment (TME), are not only closely linked to normal fibroblasts, but also can secrete a variety of substances (including exosomes) to participate in the regulation of the TME. Exosomes can play a key role in intercellular communication by delivering intracellular signaling substances (e.g., proteins, nucleic acids, non-coding RNAs), and an increasing number of studies have shown that non-coding RNAs of exosomal origin from CAFs are not only closely associated with the formation of the CRC microenvironment, but also increase the ability of CRC to grow in metastasis, mediate tumor immunosuppression, and are involved in the mechanism of drug resistance in CRC patients receiving. It is also involved in the mechanism of drug resistance after radiotherapy in CRC patients. In this paper, we review the current status and progress of research on CAFs-derived exosomal non-coding RNAs in CRC.